The Prevalence of Self-Reported Diabetes in the Australian National Eye Health Survey. - Stuart Keel; Joshua Foreman; Jing Xie; Peter van Wijngaarden; Hugh R Taylor; Mohamed Dirani (PLoS ONE, 2017)
To present the prevalence of self-reported diabetes in Indigenous and non-Indigenous participants in the National Eye Health Survey.3098 non-Indigenous Australians aged 50-98 years and 1738 Indigenous Australians aged 40-92 years were examined in 30 randomly selected sites, stratified by remoteness. A history of diabetes was obtained using an interviewer-administered questionnaire.13.91% (431/3098) of non-Indigenous Australians and 37.11% (645/1738) of Indigenous Australians had self-reported diabetes. The age-adjusted prevalence of self-reported diabetes for non-Indigenous and Indigenous Australians was 11.49% and 43.77%, respectively (p <0.001). The prevalence of self-reported diabetes increased markedly with age (OR = 1.04 per year, p = 0.017). Indigenous Australians living in very remote areas were more likely to have self-reported diabetes than those in major city areas (OR = 1.61, p = 0.038).The prevalence of self-reported diabetes in Australia was high, with the prevalence being almost 4 times higher in Indigenous Australians compared with non-Indigenous Australians. With the prevalence of diabetes likely to increase, the results of this national survey may inform future policy, planning and funding allocation to assist in controlling the diabetes epidemic.